Rural Area Learners’ Writing Self-efficacy Development: A Qualitative and Quantitative Approaches - Jalaluddin, Ilyana (Institut Agama Islam Negeri Imam Bonjol Padang, 2017)
This case study aimed to evaluate the rural area learners’ writing self-efficacy using two different approaches which are qualitative and quantitative approach. It involved three form four students and a teacher for six months. In this study, the learners’ writing self-efficacy was investigated using a combination of quantitative and qualitative (classroom observation). Classroom observation was based on three characteristics: persistence in accomplishing language tasks, self-awareness of English proficiency, and willingness to engage in language activities. These characteristics which were concept of self-efficacy. This study did not focus on the score of WSE scales alone but also placed a heavy emphasis on the perceptions and actions of the form four students and teacher. Altogether, 15 non-participant classroom observations, 10 interviews with each of the three students and 10 teacher’s interviews were carried out to understand the participants’ self-efficacy phenomena in their learning to write. Findings showed that the combination of different method of collecting data for writing self-efficacy was a feasible way in explaining rural learners’ writing self-efficacy development.